2013
DOI: 10.1158/1078-0432.ccr-13-0616
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment Decreases Microbial Burden Associated with Pseudomyxoma Peritonei and Affects β-Catenin Distribution

Abstract: Purpose: Pseudomyxoma peritonei is an understudied cancer in which an appendiceal neoplasm invades the peritoneum and forms tumor foci on abdominal organs. Previous studies have shown that bacteria reside within pseudomyxoma peritonei tumors and mucin. Thus, we sought to analyze the effect of antibiotics on bacterial density and b-catenin expression within pseudomyxoma peritonei samples.Experimental Design: The study included 48 patients: 19 with disseminated peritoneal adenomucinosis (DPAM) and 29 with perito… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Importantly, the survival rate of LN positive patients within the pilot group that received antibiotic therapy was effectively the same as those that did not receive antibiotics (data not shown). Importantly, an additional recent study from our group showed that antibiotic treatment significantly reduced the number of bacteria found in PMP tissue [28]. Thus, en masse our results support our hypothesis that eliminating bacteria from the affected peritoneal tissue prior to metastasis may improve survival of patients with PMP disease.…”
Section: Resultssupporting
confidence: 88%
“…Importantly, the survival rate of LN positive patients within the pilot group that received antibiotic therapy was effectively the same as those that did not receive antibiotics (data not shown). Importantly, an additional recent study from our group showed that antibiotic treatment significantly reduced the number of bacteria found in PMP tissue [28]. Thus, en masse our results support our hypothesis that eliminating bacteria from the affected peritoneal tissue prior to metastasis may improve survival of patients with PMP disease.…”
Section: Resultssupporting
confidence: 88%
“…Additionally, Gilbreath et al ( 3 ) identified a core microbiome present in PMP tumors that is conserved among examined patients. Moreover, a recent study by Semino-Mora et al ( 4 ) suggested higher bacterial density and higher expression of the MUC2 mucin associated with more malignant forms of PMP. It was further shown that the treatment of patients with antibiotics targeting H. pylori prior to cytoreductive surgery reduces the peritoneal bacterial density and decreases nuclear β-catenin, a known biomarker of carcinogenesis.…”
Section: Genome Announcementmentioning
confidence: 96%
“…To the best of our knowledge, no research has been done thus far on the influence of CAM on the Wnt/β-catenin signalling pathway. In this connection, Semino-Mora et al reported that β-catenin levels were decreased in the cytoplasm, the cell nuclei, and the mucin-associated cells while β-catenin levels within membranes increased in pseudomyxoma peritonei patients after H pylori eradication treatment containing CAM, providing potential protection against cell detachment, cellular invasion, and metastasis [83]. …”
Section: Mechanism Of Actionmentioning
confidence: 99%